Polygenic prediction of occupational status GWAS elucidates genetic and environmental interplay in intergenerational transmission, careers and health in UK Biobank - Evelina T. Akimova; Tobias Wolfram; Xuejie Ding; Felix C. Tropf; Melinda C. Mills (Nature Human Behaviour, 2024)
Socioeconomic status (SES) impacts health and life-course outcomes. This genome-wide association study (GWAS) of sociologically informed occupational status measures (ISEI, SIOPS, CAMSIS) using the UK Biobank ( N 0.167em=0.167em273,157) identified 106 independent single-nucleotide polymorphisms of which 8 are novel to the study of SES. Genetic correlations with educational attainment ( r g 0.167em=0.167em0.96–0.97) and income ( r g 0.167em=0.167em0.81–0.91) point to a common genetic factor for SES. We observed a 54–57% reduction in within-family predictions compared with population-based predictions, attributed to indirect parental effects (22–27% attenuation) and assortative mating (21–27%) following our calculations. Using polygenic scores from population predictions of 5–10% (incremental R 2 0.167em=0.167em0.023–0.097 across different approaches and occupational status measures), we showed that (1) cognitive and non-cognitive traits, including scholastic and occupational motivation and aspiration, link polygenic scores to occupational status and (2) 62% of the intergenerational transmission of occupational status cannot be ascribed to genetic inheritance of common variants but other factors such as family environments. Finally, links between genetics, occupation, career trajectory and health are interrelated with parental occupational status.
Keywords: 300